2021
DOI: 10.1186/s12884-021-04216-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intra-partum Oxytocin on neonatal encephalopathy: a systematic review and meta-analysis

Abstract: Background Oxytocin is widely used for induction and augmentation of labour, particularly in low- and middle-income countries (LMICs). In this systematic review and meta-analysis, we examined the effect of intra-partum Oxytocin use on neonatal encephalopathy. Methods The protocol for this study was registered with PROSPERO (ID: CRD42020165049). We searched Medline, Embase and Web of Science Core Collection databases for papers published between Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Augmentation of labor was found to be an independent predictor of perinatal outcome. Similarly, a recent review by Burgod et al, 26 found intra-labor use of oxytocics to be associated with neonatal encephalopathy. Therefore, augmentation of labor must be done with caution.…”
Section: Discussionmentioning
confidence: 84%
“…Augmentation of labor was found to be an independent predictor of perinatal outcome. Similarly, a recent review by Burgod et al, 26 found intra-labor use of oxytocics to be associated with neonatal encephalopathy. Therefore, augmentation of labor must be done with caution.…”
Section: Discussionmentioning
confidence: 84%
“…This is in line with observational studies from high-income countries, but with more severe consequences. 6 , 7 , 8 , 62 , 63 Suboptimal monitoring of FHR and contractions, as described in the studies, is likely mediating the severity of risks. The influence of substandard care was, however, not assessed in the studies.…”
Section: Commentsmentioning
confidence: 92%
“… 1 Observational studies, from high-income countries mainly, suggest an association with acidemia, low Apgar score, and neonatal encephalopathy (NE). 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…Hence, brain injury might occur from intermittent cerebral hypoxia during active labor, especially if labor is medically augmented 41 -"vulnerable baby in the womb." Preclinical models of growthrestricted animals and intermittent umbilical cord occlusion 42 may represent this scenario.…”
Section: Jama Network Open | Pediatricsmentioning
confidence: 99%